Comparative study on combustion and emission characteristics of methanol/gasoline blend fueled DISI engine under different stratified lean burn modes - Miaomiao Zhang; Jianbin Cao (Fuel Processing Technology)
Combining stratified lean-burn techniques with methanol offers a promising path to achieving high efficiency and low emissions in direct-injection spark-ignition (DISI) engines. This work compares the stratified and homogeneous-stratified lean-burn characteristics of methanol/gasoline fuels on a DISI engine. Combustion and emissions characteristics under two stratified lean-burn strategies were investigated. The results indicate that compared to double-injection stratified lean-burn (DISL), single-injection stratified lean-burn (SISL) leads to more timely combustion, which deteriorates more slowly as the excess air ratio increases. Using M20 fuel with SISL achieves a higher tolerance for air dilution. At the same excess air ratio, SISL results in higher maximum in-cylinder pressure and combustion temperature, but lower exhaust temperature. The economic zone for SISL occurs with M40 fuel at λ = 1.3–1.6, whereas DISL's economic zone is within λ = 1.1–1.3. When λ is below 1.5, SISL produces higher hydrocarbon (HC) emissions but lower nitrogen oxides (NOx) emissions. However, as λ exceeds 1.5, HC emissions from DISL increase sharply while NOx emissions decrease significantly. The particle concentration from SISL is at least an order of magnitude higher than that from DISL, with particle size distribution forming a unimodal curve centered around accumulation mode particles. Conversely, DISL exhibits a quasi-bimodal distribution.